(untitled) (Polish Yearbook of International Law, 2016)
This article presents the Polish practice of promulgation of international agreements since the end of World War II. It shows that the practice is at variance with the law and makes it difficult to determine the current legal situation vis-à-vis international agreements in Poland. In the conclusions the author puts forward de lege ferenda proposals which could improve the Polish promulgation practice.